(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A new planktonic foraminiferal species, Hedbergella rhinoceros, from the Late Aptian to the Early Albian sediments of the Marne a Fucoidi formation (Umbro —Marchean Apennines, central Italy) is described and illustrated.